Evaluation of Serum Procalcitonin and Other Kidney Function Test in Patients with Large Renal Stone - Walaa Ahmed Al-Jedda, Shatha Al-Khateeb, Asawir Abdulrazaq Hamad, Ahmed A. Al Samaraee, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Renal stone disease is a main cause for acute kidney injury . Renal stone can damage the tubular epithelial cells, which can lead to functional loss of the renal parenchyma. Procalcitonin (PCT) is a peptide precursor of the hormone calcitonin . PCT levels are marker for determine if a patient has an infection , bacteria selectively aggregate to crystal and that bacteria are associated with an increased number of crystal-crystal agglomerations. Bacteria-crystal aggregates bind to the tubular epithelium resulting in expression of stone matrix proteins in either renal tubular epithelium or inflammatory cells. Objective: To estimate serum procalcitonin (PCT) in primary renal stone patients and compare it with secondary renal stone group when renal stone size ≥ 1.5 cm. Subjects, Materials and Methods: This Cross-sectional Study was designed incorporation with college of Medicine , Mustansiriya university , chemistry and biochemistry Department . Samples were taken from Al Yarmouk teaching hospital in Bagdad , urology department . A total number of eighty eight (88) patients were registered (44 male ) and (44 female ) aged between (30-40) years. The total subjects were divided into two groups:Group I : Patients with Primary Renal Stone , Group II: Patients with Recurrent(secondary) renal stone . Results: Analysis of variance for serum PCT were significant , p ≤0.0001, indicating there were significant difference in serum PCT among renal stone size in primary renal stone group and recurrent(secondary) renal stone group . Conclusion: Serum procalcitonin increased significantly in patients with recurrent renal stone disease ,therefore, it is considered as a predictor of kidney stone disease. Keywords: Serum Procalcitonin , Primary Renal stone , Secondary Renal stone , Serum uric acid , and Serum Albumin